2021
DOI: 10.3390/life11020087
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Sound Tolerance in Tinnitus Patients

Abstract: (1) Background: Decreased sound tolerance is a significant problem in tinnitus sufferers. The aim of the study was to evaluate the relationship between tinnitus and decreased sound tolerance (hyperacusis and misophonia). (2) Methods: The study sample consisted of 74 patients with tinnitus and decreased sound tolerance. The procedure comprised patient interviews, pure tone audiometry, impedance audiometry, measurement of uncomfortable loudness levels, and administration of the Hyperacusis Questionnaire, Tinnitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…On the other hand, decreased sound tolerance was persistent in adolescents with normal hearing and tinnitus who did not recover during 1-year follow-up (8). To diagnose decreased sound tolerance, thorough history taking, audiological assessment, and psychological evaluation are necessary to exclude the possibility of misophonia (9). In a recent study, where tinnitus patients and a control group of patients with normal or symmetric hearing loss were enrolled, patients with unilateral tinnitus had significantly lower LDLs than the control group (10).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, decreased sound tolerance was persistent in adolescents with normal hearing and tinnitus who did not recover during 1-year follow-up (8). To diagnose decreased sound tolerance, thorough history taking, audiological assessment, and psychological evaluation are necessary to exclude the possibility of misophonia (9). In a recent study, where tinnitus patients and a control group of patients with normal or symmetric hearing loss were enrolled, patients with unilateral tinnitus had significantly lower LDLs than the control group (10).…”
Section: Discussionmentioning
confidence: 99%
“…A major confound is that clinical studies are nearly entirely self-reported and based on patient reported outcomes over the last week or month. Large clinical studies have found a significant positive correlation between tinnitus and hyperacusis ( Cederroth et al, 2020 ; Raj-Koziak et al, 2021 ). Another study found that hyperacusis percept shows a positive correlation for the persistence of tinnitus ( Refat et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a recent meta-analysis of clinical reports from the Cochrane library shows that tinnitus is one of the more common side effects for CF patients with recurrent AG treatments ( Smith et al, 2018 ). Hyperacusis is under-reported clinically but is known to be debilitating and comorbid with tinnitus ( Pienkowski et al, 2014 ), increasing with the number of years a patient has experienced tinnitus ( Raj-Koziak et al, 2021 ; Refat et al, 2021 ). Thus, it is important for AG-induced auditory dysfunctions to be further investigated in animal models to develop potential therapeutics for these diseases of maladaptive plastic change.…”
Section: Introductionmentioning
confidence: 99%
“…The ReSound Tinnitus Relief app was tested in our pilot study, and because of promising results, it was used again in this study [26,27]. The app was created in 2014 and is available on the Google Play Store and the App Store.…”
Section: Resound Tinnitus Relief Appmentioning
confidence: 99%
“…As the operation of the app on both platforms was the same, in our study we did not control which operating system the participants used. This particular app was chosen because it is free, has a menu in Polish, and has already been described in the literature [24,25,27,28]. The main function of the app is to generate various acoustic signals.…”
Section: Resound Tinnitus Relief Appmentioning
confidence: 99%